Microfinance, EU Structural Funds and Capacity Building for Managing Authorities A Comparative Analysis of European Convergence Regions - Pes, Giovanni Nicola; Porretta, Pasqualina; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2016)
This book is open access under a CC BY license. This book presents a study of capacity building and structural funds in public managing authorities for the microcredit sector. .
Keywords: Economics; Management science; Economic policy; Economics; Economic Policy; Economics, general; Electronic books